2021
DOI: 10.1002/pssb.202000538
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Topological Edge Defects on Spin Transport Properties of Zigzag Graphene Nanoribbons

Abstract: Herein, the spin‐dependent transport properties of a zigzag graphene nanoribbon (zGNR) with edges decorated with a fluoranthene group are studied. Atomically perfect zigzag edge, including phenyl‐edge functionalization, was synthesized by Ruffieux et al. in a bottom‐up chemical technique. By performing nearest‐neighbor tight‐binding model in combination with Landauer formalism and Green's function approach, as well as considering Coulomb electronic interaction computed both with density functional calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Strong backscattering may emerge depending on the edge and defect type of nanoribbons [30]. Besides, the quantum transport in nanoribbons is usually concerned with the treatment of edges [31][32][33][34][35][36][37]. More studies may be necessary to better understand the quantum transport of topological edge states in nanoribbons.…”
Section: Introductionmentioning
confidence: 99%
“…Strong backscattering may emerge depending on the edge and defect type of nanoribbons [30]. Besides, the quantum transport in nanoribbons is usually concerned with the treatment of edges [31][32][33][34][35][36][37]. More studies may be necessary to better understand the quantum transport of topological edge states in nanoribbons.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic transport of graphene nanoribbons (GNRs) has been widely investigated during the past two decades [1][2][3][4][5][6][7][8][9] due to their potential application for designing future electronic device, such as field-effect transistors [10][11][12] and bio-sensing device [13]. Numerous previous studies have shown that the GNRs with zigzag edges (ZGNRs) exhibits metallic feature while two-thirds of armchair edged GNRs (AGNRs) are semiconducting with a small energy bandgap opening and the other one-third maintains metallic [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much effort [18][19][20][21][22][23][24][25] has focused on the fundamental question of the bandgap engineering in GNRs because the absence of energy gap limits its application on optoelectronic devices. Chemical functionalization [3,[25][26][27] on surface or edges of GNRs can effectively modify the electronic structure and then open a transport gap. Edge roughness [18,21,28] has also been widely studied as an important way to affect the conductance of GNRs.…”
Section: Introductionmentioning
confidence: 99%